THE LOAD BEARING CAPACITY OF GLULAM BEAMS WITH NOTCHES AT THE SUPPORT (Collection of scientific works «Modern structures of metal and wood», 2020)
One of the methods of reducing the construction height of the coating or overlap using glued wooden beams, as well as the connection along their length is to perform undercuts in the support nodes. The same method is used in the design of beam ceilings, where the support of secondary  beams  on  the  main  ones  is  carried  out  in  pre-selected  sockets  in  both  the  main  and secondary  beams.  As  for the calculation of such  nodes, the normative documents only provide  a calculation method for the case when the support nodes are cut with a bevel, or strict restrictions are set  regarding  the  depth  of  cutting  a  beam  without  a  bevel  on  the  side  of  the  stretched  zone  in relation to its height. In addition, a number of regulatory documents recommend installing glued or screwed rods in the pruning area, but no data on their calculation is provided. Therefore, the aim of this  research  was  to  develop  a  model  allowing  to  estimate  the  carrying  capacity  of  supporting assemblies of wooden glued beams with various depths of cut according to the height of the cross-section, and reinforcements in the form of glued perpendicular to the fiber steel rods. To achieve this goal, experimental and theoretical studies of fragments of beam support units were performed using  methods  of  fracture  mechanics.  Theoretical  studies  were  performed  using  a  program  that implemented  the  finite  element  method  and  implemented  a  procedure  for  determining  stress intensity coefficients. As a result of numerical studies, according to the proposed method based on the use of the failure criterion, the regularities of changes in the bearing capacity depending on the ratio of the depth of the inset and the diameter of the glued reinforcing rods are determined. As a result of tests of full-scale fragments of support nodes of beams with undercutting, the reliability of the accepted method of numerical research and the developed model for determining the bearing capacity  of  nodes  was  confirmed.  Based  on  the  obtained  research  results,  it  was  found  that  the presence of undercutting in the support nodes of wooden glued beams on the side of the stretched edge significantly reduces their load – bearing capacity, and the installation of two reinforcing steel rods with a diameter of 16 mm to 20 mm glued across the wood fibers at a distance of at least three diameters from the vertical face of the undercut increases the load-bearing capacity of the node by 8 to 10 times, compared to nodes without reinforcing rods.